Analisis Kepadatan Jalan Puloh Me Kabupaten Bireuen Dengan Pengujian Sandcone: Analisis Kepadatan Jalan Paloh Me Kabupaten Bireuen Dengan Pengujian Sandcone - Fahmi, Mirza; Bahri, Syamsul; Kumita (Jurnal Rekayasa Teknik dan Teknologi, 2024)
Road construction structure it is necessary to have the density of the road foundation layer and soil that meet the requirements, for this reason a density test must be carried out. Road density analysis was carried out in the Road improvement Project using the Sandcone method. The work procedure carried out is to determine the physical properties of the soil and look for the degree of soil density. This study aims to determine the degree of road density with a sandcone so that we can find out what the soil density value. From the results of tests carried out Jalan Paloh Me, Ganda Pura District, Bireuen Regency, it was found that the soil was classified as silt or loamy gravel and sandy, the degree of density ranged from 120.20% - 122.73%. According to the specification requirements of SNI 03-2008-1992 the recommended degree of soil density is 95%. From the results of the tests that have been carried out, it can be concluded that the soil density in the field has reached the specified soil density requirements because the average degree of density in the field on road